2021
DOI: 10.1002/eem2.12161
|View full text |Cite
|
Sign up to set email alerts
|

Yolk–Shell P3‐Type K0.5[Mn0.85Ni0.1Co0.05]O2: A Low‐Cost Cathode for Potassium‐Ion Batteries

Abstract: Low‐cost preparation methods for cathodes with high capacity and long cycle life are crucial for commercializing potassium‐ion batteries (PIBs). Presently, the charging/discharging strain that develops in the active cathode material of PIBs causes cracks in the particles, leading to a sharp capacity fade. Here, to abate the strain release and the need for an industrially relevant process, a simple low‐cost co‐precipitation method for synthesizing yolk–shell P3‐type K0.5[Mn0.85Ni0.1Co0.05]O2 (YS‐KMNC) was repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…[ 54 ] One typical structure is introduced void space in heterostructures, such as hollow structure, bowl‐like structure, and yolk‐shell structure. [ 55,56 ] The void space can mitigate the internal stress caused by violent volume expansion, leading to excellent cycling performance (Figure 5b). [ 57 ] Another typical structure is nicely arranged array structures formed by growing heterostructures on substrates, such as carbon cloth, nickel foam, nickel foil, and copper foil.…”
Section: Design Strategies Of Heterostructures For Energy Storage Applicationsmentioning
confidence: 99%
“…[ 54 ] One typical structure is introduced void space in heterostructures, such as hollow structure, bowl‐like structure, and yolk‐shell structure. [ 55,56 ] The void space can mitigate the internal stress caused by violent volume expansion, leading to excellent cycling performance (Figure 5b). [ 57 ] Another typical structure is nicely arranged array structures formed by growing heterostructures on substrates, such as carbon cloth, nickel foam, nickel foil, and copper foil.…”
Section: Design Strategies Of Heterostructures For Energy Storage Applicationsmentioning
confidence: 99%
“…These problems can be solved by adjusting the size of cathode materials and designing hollow micro/nano structures and special structures. 70,[84][85][86] The hollow micro/nano structure materials have high specific surface area and enough Na + storage sites. As a result, it can improve the rate performance and cycling stability of the cathode by effectively shortening the diffusion length of Na + , providing buffer for the volume strain generated in the cycling process, and enhancing the ionic conductivity.…”
Section: Micro/nano Structure Architecturementioning
confidence: 99%
“…These problems can be solved by adjusting the size of cathode materials and designing hollow micro/nano structures and special structures. 70,84–86…”
Section: Strategies For Structural Stabilizationmentioning
confidence: 99%
“…The 3D framework with uniform carbon coating provided rapid K-ion diffusion channels and a 3D electron transport network during K + extraction/insertion. Recently, Hao et al [162] designed a microscale yolk-shell P3-K 0.5 [Mn 0.85 Ni 0.1 Co 0.05 ]O 2 (YS-KMNC) cathode which delivered a discharge capacity of 96 mAh g −1 at 20 mA g −1 and showed excellent cyclability with 80.5% capacity retention over 400 cycles at 200 mA g −1 . Analysis of the strain variation during volume expansion of the cathode materials using finite element analysis (Figure 15c,d) revealed that the yolk-shell structured KMNC experienced lower internal stress than conventional KMNC.…”
Section: Morphology Designmentioning
confidence: 99%